Le pouvoir monétaire international : le statut international d’une monnaie est-il un instrument de puissance ou un facteur de fragilité? - Grjébine, André (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1979)
The problem of replacing the dollar as the principal instrument of international fund transfers, both official and private, is becoming increasingly acute. In attempting to assess to what extent the potential « successors » to American currency - the Deutsche Mark, S.T.R., crown - can, claim to be able at least to support it if not to replace it, it would be appropriate to identify the conditions in which the « internationalization » of first, the Pound sterling, and secondly, the dollar, was accomplished. Such an analysis makes it possible to consider the advantages and disadvantages inherent upon the use of a national currency as an international currency both for the country issuing that currency as well as for the international community. Experience shows, in fact, that « international monetary power » is a two-edged sword which can, undoubtedly be used to promote the « imperialist » aspirations of a state but which can also be shown to be a potential fact or for weakening its economy and bringing about the eventual undermining of the lutter.This state of affairs explains the reservations of the Germon, Japanese and Swiss monetary authorities with respect to sharing with the United States the burden of the « international monetary power » that the latter had exercised for several decades. These reservations however will likely not be sufficient to prevent the progressive internationalization of a currency such as the Deutsche Mark ... unless extensive measures are taken quickly to ensure the international growth of exclusively international instruments such as S.T.R. and the crown.